Impact of acupuncture on mortality in patients with disabilities and newly diagnosed heart failure: a nationwide cohort study - Hyungsun Jun; Dasol Park; Jae-Uk Sul; Moon Joo Cheong; Haerim Kim; Inae Youn; Jungtae Leem; Jungtae Leem; Jungtae Leem (Frontiers in Medicine)
ObjectivePeople with disabilities have high rates of cardiovascular diseases and mortality, and heart failure can worsen their condition. Therefore, preventing and managing cardiovascular diseases is particularly important for this population. Although acupuncture has been used for heart failure, research on its impact on mortality is limited. Given the unique pathophysiological characteristics of people with disabilities, this study aimed to evaluate the effect of acupuncture on mortality in those newly diagnosed with heart failure.MethodsThis retrospective cohort study used data from the Korean National Health Insurance Service, focusing on people with disabilities diagnosed with heart failure between 2014 and 2016. Acupuncture exposure within 1 year of diagnosis was assessed by dividing the participants into acupuncture-exposed and non-exposed groups. Propensity score matching (PSM) was used to adjust for group differences, and all-cause mortality was tracked for 3 years. Cox proportional hazard models were employed to calculate hazard ratios (HRs) and confidence intervals (CIs). Dose-response relationships were also analyzed by dividing acupuncture frequency into quartiles.ResultsAfter PSM, 21,001 individuals were included in both groups. The acupuncture-exposed group had a 20% lower risk of all-cause mortality (adjusted HR 0.80, 95% CI 0.76–0.84) than those in the non-exposed group. Higher acupuncture doses were associated with a greater reduction in mortality, with the highest dose group showing a 36% lower risk (adjusted HR 0.64, 95% CI 0.58–0.69) than those in the non-exposed group. The subgroup analysis showed a consistent reduction in mortality across most groups, particularly in women, older adults, higher-income individuals, and those with severe disabilities.ConclusionThis study suggests that acupuncture exposure is associated with reduced mortality in people with disabilities who are newly diagnosed with heart failure. While several limitations exist, we highlight the potential role of acupuncture in managing cardiovascular diseases in this population and encourage further research to support healthcare policies.